Interpretation of the Stern-Gerlach experiment by means of classical physics - Grēve, Juris (Physics essays, 2016)
Some postulates of quantum mechanics, inferred from essential physics experiments, have no explanation within the framework of classical physics. Moreover, some postulates are manifestly contrary to the concepts of classical physics. By researching the original descriptions of both the ferromagnetic sample studies and the experiments with atomic beams, it can be seen that misunderstandings and hasty conclusions are due to improper use of scale as well as ignoring the effect of particle interaction in the analysis and explanations of important experiments. This article analyzes the studies of the discrete spatial orientation of atomic magnetic moments (spatial quantization) in the presence of an external magnetic field. It is concluded that the results of the Stern-Gerlach experiment are subject to the laws of classical physics, and therefore that cannot serve as proof of the existence of the intrinsic spin of an electron. An explanation of the anomalous Zeeman effect within the framework of classical physics is offered.